Minor furanocoumarins and coumarins in grapefruit peel oil as inhibitors of human cytochrome P450 3A4 - César, Thaïs B.; Manthey, John A.; Myung, Kyung (American Chemical Society (ACS), 2009)
A new cyclic acetal (1) of marmin (6′,7′-dihydroxy-7- geranyloxycoumarin), two new cyclic acetals (5, 6) of 6′,7′- dihydroxybergamottin, and the known compounds marmin (2), 7-geranyloxycoumarin (3), bergamottin (4), and 6′,7′-dihydroxybergamottin (7) were isolated from grapefruit peel oil. All compounds were tested for inhibitory activity against intestinal cytochrome P450 3A4, an enzyme involved in the grapefruit/drug interactions in humans. Coumarins (1-3) exhibited negligible inhibitory activity, while the furanocoumarins (4-7) showed potent in vitro inhibitory activity with IC50 values of 2.42, 0.13, 0.27, and 1.58 μM, respectively.